Characteristics of acute ischemic stroke in patients with Nephrotic syndrome - Wen-Yi Huang; Chun-Wei Chang; Kuan-Hsing Chen; Chien-Hung Chang; Hsiu-Chuan Wu; Kuo-Hsuan Chang (Renal Failure, 2023)
The incidence of ischemic stroke (IS) is higher in nephrotic syndrome (NS) patients compared to general population. However, there is limited information on the specific characteristics to stroke patients with NS. In this study, we aimed to examine the clinical manifestations of acute IS in a large group of NS patients, comparing to those without NS. We conducted a retrospective cohort study to compare the clinical presentations of acute IS in patients with and without NS. This study was a multi-institutional study and used data from Chang Gung Research Database of Taiwan from 1 January 2001, to 31 December 2017. A total of 233 IS patients with NS and 1358 IS patients without NS were enrolled. The median age of participants was 68 (range: 59–79) years. The risk of dependent functional status (modified Rankin Scale score≧3) after IS was higher in NS patients compared to those without NS (Odd ratio (OR) 4.02, 95% confidence interval (CI) 2.39 to 6.76, p < 0.001), particularly in stroke subtypes as small-artery occlusion (OR 8.02, 95% CI 3.94 to 16.32, p < 0.001), and stroke of undetermined etiology (OR 2.47, CI 1.06 to 5.76, p = 037). The risks of mortality or stroke recurrence within 30 days were similar between the two groups for all stroke subtypes. In conclusion, NS was associated with a higher risk of functional dependence following IS. Intensive treatment and rehabilitation should be considered for IS patients with NS.